THE OBJECTIVES OF THE CONCEPT OF JIHAD IN ISLAM. - Sing, David Emmanuel (Journal of Dharma, 2002)
The picture of Islam as a circle gives us some very useful hints about what it is that makes a certain way of life, a certain set of beliefs and practices, Islamic. I juxtapose the Islamic circle with a Christian circle and ask what are some of the things that define the one circle as Islamic and the other as Christian. Iobserve that the circles do not naturally come together. This means that the believers within either circle do not find it natural to associate with one another. The things that keep the circles apart have generally to do with theology, role models, scriptures, ethnicity, race, history, politics, economics and so on. It is obvious that there are multiple factors that keep the circles of religions apart.